Global threat assessment 2009 - Rohan Gunaratna (2009)
Whilst 2009 will continue to see terrorism as the pre-eminent security threat, much can be done by the West to reach out to alienated communities, especially in the Muslim world. The United States should remove Muslim mistrust and suspicion of America's intentions. Without Muslim public support, the fight against terrorism and extremism will be lost.